Influência dos Dados de Radiação no Dimensionamento de Sistemas Fotovoltaicos - Mougueira, Carlos (2009)
Solar irradiantion from various sources are analysed and differences discussed with respect to sizing of pv-systems. Differences up to 49% can be observed between solar irradiance for the location Évora, Portugal which are caused in part by interannual variability (especially the amount and frequency of clouds) and in part by different methods used in the process of providing data from different sources.